2021
DOI: 10.1186/s13756-021-00970-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined antibiotic stewardship and infection control measures to contain the spread of linezolid-resistant Staphylococcus epidermidis in an intensive care unit

Abstract: Background The unrestricted use of linezolid has been linked to the emergence of linezolid-resistant Staphylococcus epidermidis (LRSE). We report the effects of combined antibiotic stewardship and infection control measures on the spread of LRSE in an intensive care unit (ICU). Methods Microbiological data were reviewed to identify all LRSE detected in clinical samples at an ICU in southwest Germany. Quantitative data on the use of antibiotics with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…WGS and subsequent extraction of the seven MLST targets identified all 15 LRSE isolates as ST2. This ST is frequently associated with nosocomial infections and blood stream infections [ 8 , 12 , 26 , 28 ]. In-depth analysis revealed that the SCC mec type III was detected in all isolates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…WGS and subsequent extraction of the seven MLST targets identified all 15 LRSE isolates as ST2. This ST is frequently associated with nosocomial infections and blood stream infections [ 8 , 12 , 26 , 28 ]. In-depth analysis revealed that the SCC mec type III was detected in all isolates.…”
Section: Resultsmentioning
confidence: 99%
“…For all WGS datasets, we utilized the software SeqSphere + (Ridom GmbH, Münster, Germany, version 9.0.0) to compare coding regions in a gene-by-gene approach, i.e., core genome multilocus sequence typing (cgMLST), as described previously [ 25 ]. To analyze genetic relatedness, we used the recently published cgMLST scheme for S. epidermidis [ 26 ]. Clonal relationship of genotypes is here displayed using a minimum spanning tree algorithm calculated by the same software and is rated as closely related if genotypes differ in ≤6 alleles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus complex [ 4 , 5 ]. Device-related infections are one of the most common manifestations of CoNS infections, causing high morbidity and mortality [ 6 , 7 ]. With the advent of modern tools in routine microbiological diagnostics such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), pathogen detection has experienced a remarkable refinement within the past decade [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coagulase-negative staphylococci (CoNS) are abundant inhabitants of the human skin and the mucosa with limited pathogenicity [1,2], as opposed to Staphylococcus aureus [3] and other members of the S. aureus complex [4,5]. Device-related infections are one of the most common manifestations of CoNS infections, causing high morbidity and mortality [6,7]. With the advent of modern tools in routine microbiological diagnostics such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), pathogen detection has experienced a remarkable refinement within the past decade [8,9].…”
Section: Introductionmentioning
confidence: 99%